The Role of Low Soil Temperature for Photosynthesis and Stomatal Conductance of Three Graminoids From Different Elevations - Göbel, Leonie; Coners, Heinz; Hertel, Dietrich; Willinghöfer, Sandra; Leuschner, Christoph (Frontiers in Plant Science, 2019)
In high elevation grasslands plants can encounter periods with high air temperature while the soil remains cold, which may lead to a temporary mismatch in the physiological activity of leaves and roots. In a climate chamber experiment with graminoid species from three elevations (4400, 2400, 250 m a.s.l.), we tested the hypothesis that soil temperature can influence photosynthesis and stomatal conductance independently of air temperature. Soil monoliths with swards of Kobresia pygmaea (high alpine), Nardus stricta (lower alpine) and Deschampsia flexuosa (upper lowland) were exposed to soil temperatures of 25, 15, 5 and -2 °C and air temperatures of 20 and 10 °C for examining the effect of independent soil and air temperature variation on photosynthesis, leaf dark respiration, stomatal conductance and transpiration. Soil frost (-2 °C) had a strong negative effect on gas exchange and stomatal conductance in all three species, independent of the elevation of origin. Leaf dark respiration was stimulated by soil frost in D. flexuosa, but not in K. pygmaea, which also had a lower temperature optimum of photosynthesis. Soil cooling from 15 to 5 °C did not significantly reduce stomatal conductance and gas exchange in any of the species. We conclude that all three graminoids are able to maintain a relatively high root water uptake in cold, non-frozen soil, but the high-alpine K. pygmaea seems to be especially well adapted to warm shoot−cold root episodes, as it has a higher photosynthetic activity at 10 than 20 °C air temperature and does not up-regulate leaf dark respiration upon soil freezing, as was observed in the grasses from warmer climates.